Metodologia para o tratamento acústico de salas e estudo de caso - Zin Almas, Bruno (Universidade Federal de São Carlos, 2025)
This paper describes a methodology for acoustic treatment of rooms, as well as a relevant theoretical introduction to the activity in question, through a bibliographic study of the area. To apply the acquired knowledge, a treatment of a room with perceptibly low acoustic quality was carried out, through simulations, on-site tests, and application of different solutions, with a specific solution being the production and testing of a Helmholtz Absorber. For this purpose, hardware such as a microphone and speaker were used, and software for performing scans, data processing, and visualization of the obtained results. As a solution, measures and tools for acoustic treatment were applied, and a verification of the results obtained with such measures.
Methodology for acoustic treatment of rooms and case study
Keywords: Acústica; Tratamento acústico; Som; Absorvedor acústico; ENGENHARIAS::ENGENHARIA ELETRICA::MEDIDAS ELETRICAS, MAGNETICAS E ELETRONICAS; INSTRUMENTACAO